Knowledge, understanding and the dynamics of medical innovation - Ronnie Ramlogan; Davide Consoli (The University of Manchester, Manchester Business School, 2008)
This paper investigates the processes by which scientific knowledge is created and legitimized. It focuses on scientific developments in a branch of medicine and explores the pathways through which the growth of knowledge enables advances in medical science and in clinical practice. This work draws conceptually on evolutionary approaches to technological change. The empirical part presents a longitudinal analysis of a database of scientific publications in the field of ophthalmology over a period of 50 years. Such an exercise allows us to identify pathways of shared understanding on a disease area, and to map out distinctive trajectories followed by the ophthalmology research community. The paper also contributes to general understanding of the innovation process by supporting the notion that knowledge coordination is a distributed process that cuts across and connects complementary areas of expertise.
Keywords: 330; Medizin; Medizintechnisches Gerät; Technischer Fortschritt; Forschungskooperation; Wissenstransfer